Sosialisasi Pembuatan Kompos dari Limbah Organik Rumah Tangga - Puspita, Diah Eka; Khumaira, Khumaira; Fitri, Sri; Setyowati, Mita; Meliyanti, Meliyanti; Cibro, Tania; Malik, Abdul (Universitas Teuku Umar, 2024)
The purpose of this community service activity is to educate the community, especially housewives, on how to turn household waste into useful materials. With the knowledge provided, the participants are expected to be able to implement the knowledge in their daily actions. So that as members of the community, we can participate in environmental conservation efforts. In addition, the use of compost from organic or household waste can also be a new source of income for housewives by selling compost to friends or family in need. The use of compost also reduces the use of chemical fertilizers, which means that we have contributed to a healthier and more sustainable environment. The evaluation results of this activity showed a positive response from the participants. The questionnaire results showed that 76.67% were very interested in making compost at home. The participants plan to start creating their own composers soon (66.67%) and 93.3% want further activities.